NF-kappa B activation is involved in regulation of cystic fibrosis transmembrane conductance regulator (CFTR) by interleukin-1 beta - Cafferata, Eduardo (2001)
Fil: Cafferata, Eduardo. ANLIS Dr.C.G.Malbrán. Centro Nacional de Genética Médica Dr. Eduardo Castilla. Departamento de Genética Experimental; Argentina.